Optimized LPDA Antenna for IoT Applications. Issue 1 (1st May 2022) - Ng, W H; Tiang, S S; Lim, W H; Teng, K H; Karunamoothei, V
Abstract: In this new era of fast-growing industry revolution, IoT has become integral part of most industries. In this paper, a high directivity printed log periodic dipole array (LPDA) antenna printed on a FR4 substrate is proposed for the application of IoT communication. The simulation result of NSGA-II optimized antenna is then compared and validated with another optimization scheme, MOEA\D algorithm. The simulation results demonstrate that the proposed antenna has low sidelobe level of -13.9dB with the VSWR < 2 across the dual bandwidth of 0.3027 GHz and 5.6289 GHz from 4.2166 GHz to 4.5193 GHz and 5.8412 GHz to 11.47 GHz respectively. The proposed antenna has achieved a new low side lobe level of -13.9 dB. It is also possesses a wide bandwidth which enhanced from 2.52GHz to the dual bandwidth of 0.3027 GHz and 5.6289 GHz on 4.2166 GHz to 4.5193 GHz and 5.8412 GHz to 11.47 GHz respectively. It has a good realized gain of 8.42dBi with the increment of 1.42dBi after optimization. The multi objective genetic algorithm optimizes the realized gain, directivity, sidelobe level, bandwidth, standing wave ratio of the proposed antenna which is well suited for practical applications in physical layer IoT communication.